PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DAERAH PROVINSI KEPULAUAN RIAU DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Mulyadi (Jurnal Teknik Ibnu Sina (JT-IBSI), 2019)
This research is purposed to empirically determine the direct effect of career development towards the employees performance, work motivation towards the employees performance, career development towards job satisfaction, work motivation towards job satisfaction and job satisfaction towards the employees performance. And how to empirically determine the indirect effect of career development towards the employees performance by job satisfaction and work motivation towards the employees performance by job satisfaction.This research took the sample of 160 employees that is related with Sekretariat Daerah Provinsi Kepulauan Riau. The data were analysed using the “Path Analysis” of the statistical software SPSS 20.This results of this research as follows career development has direct influence towards the employees performance with significant path coefficient value of 0.163 and significant at the 0.000 probability sig > α 0.05, work motivation has direct influence towards the employees performance with significant path coefficient value of 0.465 and significant at the 0.000 probability sig > α 0.05, career development has direct influence towards job satisfaction with significant path coefficient value of 0.268 and significant at the 0.000 probability sig > α 0.05, work motivation has direct influence towards job satisfaction with significant path coefficient value of 0.655 and significant at the 0.000 probability sig > α 0.05, job satisfacton has direct influence towards the employees performance with significant path coefficient value of 0.895 and significant at the 0.000 probability sig > α 0.05, career development has indirect effect on employees performance through job satisfaction with path coefficient value of (0.268 x 0.895 = 0.240) and has indirectly effect coefficients higher than ( > ) direct effect (0.240 > 0.163), work motivation has indirect effect on employees performance through job satisfaction with path coefficient value of (0.655 x 0.895 = 0.586) and has indirectly effect coefficients higher than ( > ) direct effect (0.586 > 0.465) in Sekretariat Daerah Provinsi Kepulauan Riau